DAMPAK RESTRUKTURISASI UTANG PADA KINERJA KEUANGAN PERUSAHAAN - ADE RUDIANA, DHILLA; VENUSITA, LINTANG (Jurnal Akuntansi AKUNESA, 2018)
The case of an Indonesian company that made a debt restructuring went bankrupt in the second year after the debt restructuring was carried out, and the case of a company that restructuring the same debt twice indicate of moral hazard. That phenomenon indicated that debt restructuring was only used by the company to avoid or delay default status without improving their real firm performance according to the purpose of debt restructuring at first. This study aims to determine the impact of debt restructuring on the companys financial performance in the period after debt restructuring. The research sample is the debt restructuring company players in 2012-2016 whose its shares are listed on the Indonesia Stock Exchange. The impact is seen through the presence of significant differences in financial performance before and after debt restructuring. The results showed that debt restructuring did not improve the companys financial performance.Keywords : Debt restructuring, financial performance, strategic impact, and Indonesian evidence.